2023
DOI: 10.2478/ngoe-2023-0002
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the Board of Directors and Dividend Policy: A Case Study of Banks in Western Balkans

Abstract: This paper examines the influence of the size and participation of women in the board of directors on the dividend policy of banks in Western Balkans. The research covered 104 banks, observing their dividend policy from 2017 to 2019. The dividend payout ratio was measured by the dividend policy. A relatively small number of banks paid dividends during the observation period. By applying the Fixed-Effect model, it was determined that the size of the board of directors has a statistically significant positive im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…is greater than 0.05 which means that we shall reject the alternative hypothesis. This indicate that the no relation between Board women's representation and cash dividend policy in Palestine stock exchange This is consistent withMilašinović, et al (2023).…”
supporting
confidence: 80%
See 1 more Smart Citation
“…is greater than 0.05 which means that we shall reject the alternative hypothesis. This indicate that the no relation between Board women's representation and cash dividend policy in Palestine stock exchange This is consistent withMilašinović, et al (2023).…”
supporting
confidence: 80%
“…However, the independence had a strong negative impact as indicated that the presence of members with financial experience is one of the main factors affecting the distribution of cash dividends. Muhammad, (2021) showed that there is a positive effect of Board size and diversity and a negative one for women's representation, while Milašinović, et al (2023). Unlike women's representation, which did not have a statistically significant effect, In contrast to Zeitoun, ( 2022), where companies with more women's representation in the board of directors tend to pay a higher level of cash dividends.…”
Section: Theoretical Referentialmentioning
confidence: 98%
“…The identification of factors that influence the profitability of a corporation is an important task that is put before the management and/or owners [1,2]. This becomes especially important during the emergence of different types of crises (examples of crises include the financial crisis of 2008 and the health crisis triggered by the COVID-19 pandemic) and in those sectors, such as financial, which are of vital importance for the operation of the entire economic system [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…In modern business conditions, corporate governance, together with intellectual capital, is recognized as one of the main factors in the success of corporations, but also in overall economic growth and development [7,8]. The term corporate governance refers to a set of practices, procedures, and guidelines that are employed to oversee, manage, and regulate the functioning of a corporation [5,9,10]. In other words, it represents a system of control and monitoring of the work of managers by the board of directors in order to ensure the maximization of value for shareholders and other stakeholders.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation